2022
DOI: 10.21608/mjeer.2022.128016.1049
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Photonic Crystal Topology for Appropriate Applications

Abstract: In this paper, different topologies were discussed and their effect on the design of photonic crystal applications was evaluated. They can be classified into four categories (i.e., ring resonator, selfcollimation, waveguide, and cavity-based structures). The figure of merits of each topology and its impact on design modules were explained and compared for two different applications (i.e., half-adder and decoder). Finite difference time domain (FDTD) and plane wave expansion methods are the two numerical approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…A recent paper [16] discusses the differences in characteristics between these topologies. Literature has shown that square and hexagonal lattices are commonly used [17,18], and operation can be performed in both linear and nonlinear regimes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper [16] discusses the differences in characteristics between these topologies. Literature has shown that square and hexagonal lattices are commonly used [17,18], and operation can be performed in both linear and nonlinear regimes.…”
Section: Introductionmentioning
confidence: 99%